Market orientation, cultural awareness performance of multinational firms : a case of multinational firms in Uganda - Nankya, Jameo (Kampala, 2013)
Unpublished thesis (M.Sc. ACC&FIN.) - Makerere University, 2013
Includes bibliographical references.
Keywords: Accounting -- Uganda; Investments -- Uganda